Tinjauan Penerapan TPM (Total Productive Maintenance) dengan mengukur nilai OEE (Overall Equipment Effectiveness): Berbagai Sektor Industri - Supriyati (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2025)
Total Productive Maintenance (TPM) was introduced by Seiichi Nakajima in Japan in the 1950s, inspired by the concept of Preventive Maintenance by George Smith from the United States. The initial implementation of TPM was carried out by Nippondenso, a Toyota supplier, in the 1960s, with the result of increased productivity and reduced equipment downtime. TPM evolved into a global management system that focuses on eight pillars to achieve production efficiency, reduced maintenance costs, and improved product quality. TPM has been adopted by various industries, especially Manufacturing. One of the key indicators in TPM is Overall Equipment Effectiveness (OEE), which measures availability, performance, and quality. The OEE value is influenced by six main factors (Six Big Losses), but it is not yet known more specifically the biggest problem of six big losses. For this reason, it is necessary to analyse various industrial sectors. The research shows that downtime due to machine failure is the biggest problem in 35 or 83.3% of industrial sectors. Further analysis is needed to improve the effectiveness of machinery and equipment, especially in the automotive sector which is often the focus of research. The results of the review process also have not found research related to equipment effectiveness through OEE measurements in the field of services.